Code as creative medium : a handbook for computational art and design - Levin, Golan, ....-; Brain, Tega, ....- (Cambridge : The MIT Press, 2021)
"This textbook provides artists, designers, and educators the necessary tools and curricula to employ "creative coding" in their school work and professional practice"--
Includes bibliographical references and index.
Keywords: Computer art -- Problems, exercises, etc; Computer art -- Study and teaching; Computer programming -- Problems, exercises, etc